Die Expressionisten vom Aufbruch bis zur Verfemung. - Behn, Helga; Berghoff, Gert; von der Borch, Agnes; Burger, Norbert; Dann, Otto; Dering, Peter; Fischer, Alfred M.; Froning, Hubertus; Gallwitz, Klaus; Herrmann, Barbara; Hoberg, Annegret; Kolberg, Gerhard; et al. (Ostfildern-Ruit : Verlag Gerd Hatje, 1996)
Adler, Jankel ; Amiet, Cuno ; Barlach, Ernst ; Bauknecht, Philipp ; Beckmann, Max ; Belling, Rudolf ; Bleyl, Fritz ; Blumenthal, Hermann ; Camenisch, Paul ; Campendonk, Heinrich ; Erbslöh, Adolf ; Ernst, Max ; Feininger, Lyonel ; de Fiori, Ernesto ; Freundlich, Otto ; Heckel, Erich ; Hoerle, Heinrich ; Hofer, Carl ; Jawlensky, Alexej von ; Kandinsky, Wassily ; Kaus, Max ; Kirchner, Ernst Ludwig ; Klee, Paul ; Kokoschka, Oskar ; Kolbe, Georg ; Kollwitz, Kathe ; Lehmbruck, Wilhelm ; Macke, August ; Marc, Franz ; Marcks, Gerhard ; Mataré, Ewald ; Meidner, Ludwig ; Minne, George ; Modersohn-Becker, Paula ; Müller, Albert ; Mueller, Otto ; Münter, Gabriele ; Nauen, Heinrich ; Nolde, Emil ; Pankok, Otto ; Pechstein, Max ; Scherer, Hermann ; Schmidt-Rottluff, Karl ; Schönberg, Arnold ; Scholz, Werner ; Seehaus, Paul Adolf ; Seiwert, Franz Wilhelm ; Sintenis, Renée (Renate Alice) ; Steger, Milly ; Thorn Prikker, Jan ; Thuar, Hans ; Voll, Christoph ; Wauer, William ; von Werefkin, Marianne
biografie
Die Expressionisten vom Aufbruch bis zur Verfemung, Museum Ludwig, Köln, 1. Juni 1996 bis 25. August 1996
Duits
boek